Inter‐Model Spread of North Tropical Atlantic Trans‐Basin Effect Substantially Biases Tropical Pacific Sea Surface Temperature Multiyear Prediction - Yang, Jun‐Chao; Lv, Zhen; Richter, Ingo; Zhang, Yu; Lin, Xiaopei (Geophysical research letters, 2022)
Sea surface temperature (SST) variability in the tropical Pacific (TP) has world‐wide climate and economic influences; hence, improving its prediction is of great interest. Recent modeling studies suggested that north tropical Atlantic variability can influence TP SST variability and prediction. However, models are subject to biases in both the tropical Atlantic and Pacific, and it remains an open question whether these biases affect the trans‐basin linkages and the prediction of TP SST. To investigate this issue, we apply linear inverse modeling to observations and climate models. We find that removing north tropical Atlantic forcing indeed strongly lowers TP SST multiyear prediction skills in observations and models. Models show a large spread of the Atlantic trans‐basin effect, which leads to markedly different TP SST multiyear prediction skills. Our study highlights the necessity to narrow the inter‐model spread for more reliable TP SST multiyear prediction. Plain Language Summary Tropical Pacific (TP) sea surface temperature (SST) variability is important for climate but hard to predict. Many modeling studies argued that the variability and prediction can be influenced by north tropical Atlantic trans‐basin effect, while the reliability of this argument is influenced by strong model biases. To reveal the influence of model biases in simulating the Atlantic trans‐basin modulation on TP SST prediction, we apply a commonly used tool for prediction called linear inverse modeling. We find that prediction skills of TP SST will strongly decrease without the north tropical Atlantic forcing in both observations and models. However, striking inter‐model spread exists in the strength of the Atlantic trans‐basin effect, resulting in strong inter‐model spread in TP SST multiyear prediction skills. Therefore, more efforts are needed to reduce the inter‐model spread of the Atlantic trans‐basin effect in the future. Key Points Observational evidence supports that north tropical Atlantic forcing substantially improve tropical Pacific (TP) sea surface temperature (SST) multiyear prediction Climate models show strong inter‐model spread in simulating north tropical Atlantic trans‐basin effect The spread of north tropical Atlantic forcing in climate models strongly affects TP SST multiyear prediction skills